The Effect of Stock Trading Volume and Market Capitalisation on Stock Price with Managerial Ownership as Moderator - Wijayanti, Winola; Arman, Rifqah Zakiyah; Rasyid, Syarifuddin; Darmawati, Darmawati (Transpublika Publisher, 2025)
This research investigates how stock trading volume and market capitalization impact stock prices in manufacturing companies listed on the Indonesian Stock Exchange between 2017-2019. It also explores the potential influence of managerial ownership on this relationship. Using a quantitative methodology with a correlational design, the study focuses on a sample of manufacturing companies selected via purposive sampling from the Indonesia Stock Exchange. Data was gathered from secondary sources accessed through www.idx.co.id. Analysis involved multiple linear regression and moderating regression using the Moderated Regression Analysis (MRA) approach. Results indicate that stock trading volume has a detrimental effect on stock prices, whereas market capitalization has a beneficial impact. Interestingly, managerial ownership was found not to moderate the link between trading volume and stock prices, but it did moderate the relationship between market capitalization and stock prices.